2017
DOI: 10.17511/ijmrr.2017.i04.09
|View full text |Cite
|
Sign up to set email alerts
|

Study of central line-associated bloodstream infections in intensive care unit: a prospective observational study

Abstract: Introduction: Central line associated blood stream infection (CLABSI) is a primary blood stream infection in a patient that had a central line within the 48-hour period before the development of bacteraemia and is not related to an infection at another site. It is often associated with serious infectious complications resulting in significant morbidity, increased duration of hospitalization and additional medical costs. Objective: We aimed to study the course of infection, microbiology of CLABSI, & to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 6 publications
1
1
0
Order By: Relevance
“…We observed the highest CLABSI cases in patients with a prolonged duration of central venous catheter of >11 days (56.8% of patients) with a mean of 18.13±10.02 days (Table 5 ). Our results were comparable with the findings of Rode et al, who reported nosocomial BSI in 77.58% of patients with >12 days of central venous catheter as compared to 22.42 patients with <12 days of central venous catheter [ 31 ]. The risk factors such as longer length of ICU stay and prolonged duration of central venous catheterization were statistically significant (Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…We observed the highest CLABSI cases in patients with a prolonged duration of central venous catheter of >11 days (56.8% of patients) with a mean of 18.13±10.02 days (Table 5 ). Our results were comparable with the findings of Rode et al, who reported nosocomial BSI in 77.58% of patients with >12 days of central venous catheter as compared to 22.42 patients with <12 days of central venous catheter [ 31 ]. The risk factors such as longer length of ICU stay and prolonged duration of central venous catheterization were statistically significant (Table 6 ).…”
Section: Discussionsupporting
confidence: 91%
“…The microbiology of CLABSI during this study showed S. aureus as most typical organism cultured followed by E. coli and MRCONS. Death rate during this study was zero and every one the patients become clinically well [17].…”
Section: Discussionmentioning
confidence: 72%